TERAPI REALITAS : UPAYA MEMAHAMI SELF-CONCEPT PADA MUDA-MUDI DALAM PELAYANAN GEREJA - Keris Handika; Petrus Yunianto (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2024)
Creativity is very inherent in young people, therefore it is not surprising that young people are very necessary for progress in various things, one of which is the Church becoming better, service is something fundamental in everyday life as a believer to do what God wants through service in the form of a way of life to the surroundings, and also to nature which has been created by God. It's just that there are still so many people who don't want to give themselves to do service for God either in the church or in the environment around them. An incorrect self-concept hinders young people from carrying out services. Therefore, the author helps readers how to deal with self-concept well by using descriptive qualitative methods. The author tries to describe the sources received to be continued in this writing so that readers understand how self-concept through reality therapy is one of the right solutions to understand the concept. self. So the aim of this research is to make readers understand the importance of a correct self-concept for young people to provide service.